Assessing the risk of Babesia to the United States blood supply using a risk‐based decision‐making approach: Report of AABB's Ad Hoc Babesia Policy Working Group (original report). Issue 8 (4th September 2018) - Ward, Sheila J.; Stramer, Susan L.; Szczepiorkowski, Zbigniew M.
Abstract : Recognizing the increasing threat of transfusion‐transmitted babesiosis to the US blood supply, the AABB Board of Directors tasked an Ad Hoc Babesia Policy Working Group (the Working Group) to use the Alliance of Blood Operators' risk‐based decision‐making (RBDM) framework to assess the risks and benefits of introducing Babesia donation testing in the United States. The regional nature of the Babesia microti risk added complexity to the RBDM assessment because of the unique operational and financial considerations for operators and hospitals located in endemic states. Therefore, the assessment considered safety, product availability, sector sustainability, and technology availability. After assessing safety risk, economic and operational impact, reimbursement equity, ethical considerations, and stakeholder feedback from two consultations, the Working Group concluded that a regional approach to donor screening in endemic states was appropriate because it applied the intervention where the risk was highest and appropriately allocated cost to the risk. Nucleic acid testing using a ribosomal RNA template was the recommended intervention because it was the most cost‐effective, resulted in no wasted units, and captured similar numbers of infections as antibody plus DNA‐based polymerase chain reaction. The current model for blood reimbursement was maintained but AABB was encouraged to facilitate collection of data to identify threats to sector sustainability in endemic states. Babesia expansion was acknowledged with a mechanism to regularly reevaluate what are "endemic states." Finally, given that public awareness of the Babesia threat is the first line of defense, AABB should work with appropriate agencies for general education about the health risk from B. microti .